A 10-year single-center experience with the GORE TAG conformable thoracic stent graft in the treatment of thoracic aortic disease - Skrypnik, Denis; Bischoff, Moritz; Meisenbacher, Katrin; Kronsteiner, Dorothea; Böckler, Dittmar (Journal of endovascular therapy, 2022)
Objective:The aim of this study was to report 10-year real-world single-center experience with the GORE TAG conformable thoracic aortic graft (CTAG), focusing on rupture-free survival, aortic-related reintervention, and device-related complications during midterm and long-term follow-up (FU).Methods:This retrospective study analyzes results of thoracic endovascular aortic repair (TEVAR) performed between January 2009 and December 2018. Out of 419 TEVAR procedures within this period, 194 patients (male 57.2%, 111/194), with a mean age of 65 ± 13?years, were treated with the CTAG device. Indication for TEVAR was a thoracic aortic aneurysm in 24.7% (48/194), type B aortic dissection in 32.5% (63/194), penetrating aortic ulcer 15.5% (30/194), and miscellaneous 27.3% (53/194). Emergently were operated 43.8% (85/194) patients. Median follow-up (FU) including computed tomography imaging was 43.5?months (Q1-Q3: 8.6?67.0) and was completed in 91.2% (177/194) of patients.Results:Overall survival rates were 75.8% (95% confidence interval [CI] = [0.76?0.70]) and 56.6% (95% CI = [0.57?0.50]) at 12 and 60?months, respectively. Cumulative incidence for aortic rupture was 11.9% (95% CI = [0.07?0.17]) at 60 and 90?months, respectively. Cumulative incidence for aortic-related reintervention was 27.5% (95% CI = [0.21?0.34]) at 60 and 90?months. Cumulative incidence for migration was 2.8% (95% CI = [0.004?0.05]) and 3.9% (95% CI = [0.007?0.07]) at 60 and 90?months, respectively. New endograft infections or material fatigue were not observed.Conclusions:The herein reported 10-year real-world single-center experience with the CTAG observed favorable long-term outcome. Thus, the device demonstrates appropriate persistent safety, efficacy, and clinical durability up to long-term FU in the treatment of diverse thoracic aortic pathologies.
First published online October 11, 2021
Gesehen am 06.02.2023